Analysis Of Tax Effort In Maluku Province (Panel Data Approach) - Ummi Duwila; Fahrudin Ramly; Ali Tutupoho (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Regional autonomy gives birth to fiscal decentralization, which means that each region is given the authority to manage its own regional finances. Local governments are given the authority to find sources of revenue to finance the development of their regions. One of the sources of regional revenue is Regional Original Revenue (PAD). Taxes and levies are the largest components of PAD, so the government always strives to increase tax revenue. Many factors affect tax revenue, both economic and non-economic aspects, but with all its authority, the government seeks to increase tax revenue (tax effort) every year, in order to finance development programs and the implementation of public services. This study uses secondary data in the form of panel data sourced from related institutions such as the Central Statistics Agency of Maluku Province, the APBD of each district/city. The data was analyzed using panel data regression analysis. The results of the study show that the value of GDP and the number of population have a positive and significant effect on tax revenue, either partially or simultaneously. Each district/city has a different response to tax collection when the value of GDP and population is minimal. Local governments need to make extensification and intensification efforts to increase tax revenue